Negotiating values for the science curriculum: The need for dialogue and compromise - Gribble, Susan; Rennie, Leonie; Tyson, Louise; Milne, C.; Speering, W. (2000)
Recently, a Curriculum Framework has been developed and mandated for implementation in all school systems— government, Catholic and independent— in Western Australia (WA). A statement of core shared values is a significant part of the Framework. The curriculum is divided into eight learning area statements, science being one of these. The Science Learning Area Statement, with its roots in the Australian Education Council (1994) statement on science, includes a definition of science and a rationale for teaching it in schools; major outcome statements concerned with working scientifically and developing conceptual understandings; principles for science learning, teaching and assessment; and sections about science as it relates to different phases of schooling, and how science can be integrated into other areas of the curriculum. Thirty two core shared values have been espoused as integral to the Cirriculum Framework. These values have been clustered into five main statements: a pursuit of knowledge and a commitment to achievement of potential; self acceptance and respect for self; respect and concern for others and their rights; social and civic responsibility; and environmental responsibility. One of the main tasks for us as writers of the Science Learning Area Statement was to explicate the core shared values into a description of the science curriculum. This article documents, from our point of view, the process by which a mandated set of core shared values were incorporated into a statement describing the curriculum in the science learning area. The process was under the direction of a Science Learning Area Committee. At several points, conflict, or potential conflict, about the interpretation of the core shared values in relation to science in the classroom was resolved by negotiation amongst ourselves in the first instance, the Science Learning Area Committee, and the Values Consultative Group. While the central narrative in this paper is about our journey through the process, there are the antecedent themes relating to how and why the core shared values were developed and subsequently mandated. The arising tensions, as yet unexplored, relate to how, or even whether, the values might be explicated in science classrooms. In reflecting on these tensions, we provide a re-analysis of some of the issues in school science, which of course are not new. We believe that science as taught in classrooms cannot be value-free, even when teachers believe otherwise.